PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN: Studi Kasus Pada Perusahaan Sub Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia - Hestia Nadira, - (2019)
This study aims to determine the effect of Profitability proxied with Return On Equity (ROE), Leverage proxied by Debt to Equity Ratio (DER), Firm Size proxied by Logarithm Natural Asset and Liquidity proxied by Current Ratio (CR) toward Firm Value proxied by Price to Book Value (PBV). Population in this study are manufacture companies listed on Indonesia Stock Exchange (IDX) 2014-2017. The technique of determination of the sample using the method of purposive sampling and obtained 26 sub sector consumer goods industry companies with a research period of four years to obtain 104 units of samples. Data analysis was done using Microsoft Excel 2016 and hypothesis testing in this research using Data Panel Regression Analysis with E-Views 10 program and significance level of 5%. The result of the research shows that (1) profitability (ROE) has a significant positive effect on firm value (PBV), (2) leverage (DER) has significant positive effect on firm value (PBV), (3) firm size (SIZE) no significant effect on firm value (PBV), (4) liquidity (CR) has a significant positive effect on firm value (PBV).